The role and image of a man in modern Kazakh society (based on the results of a sociological survey) (Eurasian Journal of Philology Science and Education, 2021)
The gender science studies the differences between women and men by gender. The development of this science has led to a change in attitudes and requirements for men and women in each country. The emergence of feminist movements which are originating in Germany, France, and the United States also directly influenced the development of this gender science. These changes are also reflected in the Kazakh society. Because today there are opinions in society that the image of the modern man differs from the image of the last generation man. We can say that the image of men in Kazakhstan society has undergone significant changes under the influence of economic, political, cultural, social and innovative conditions.We conducted a survey to identify this issue. During the survey, respondents answered questions about androcentrism, the equality of women and men, and what qualities should have a real man. This article analyzes the origin of the word «zhigit» and different definitions of words associated with it, and also different opinions about the role and place of men in Kazakh cognition. There are discussed deductions of foreign and domestic scholars about gender linguistics and differences in male and female speech. There is also studied information about the origin and status of gender linguistics in Kazakhstan, and the views of feminist organizations in our country, their activities and place in society. In this paper, we are analyzing the results of the survey, we will answer the questions about the image and role of the Kazakh man in modern society.